Kinetic Studies of Atom Transfer Radical Polymerisations of Styrene and Chloromethylstyrene with Poly(3-hexyl thiophene) Macroinitiator - Nattawoot Rattanathamwat; Jatuphorn Wootthikanokkhan; Nonsee Nimitsiriwat; Chanchana Thanachayanont; Udom Asawapirom (Advances in Materials Science and Engineering)
Poly(3-hexyl thiophene)-b-poly(styrene-co-chloromethylstyrene) copolymers, to be used as a prepolymer for preparing donor-acceptor block copolymers for organic solar cells, have been synthesised by reacting P3HT macroinitiators with styrene and chloromethylstyrene via three types of atom transfer radical polymerisation (ATRP) systems, which are (1) a normal ATRP, (2) activators generated by electron transfer (AGET), and (3) a simultaneous reverse and normal initiation (SR&NI). The kinetics of these ATRP systems were studied as a function of monomers to the macroinitiator molar ratio. It was found that all of the three types of ATRP systems led to first order kinetics with respect to monomers. The highest rate constant (k) of 3.4 × 10−3 s−1 was obtained from the SR&NI ATRP system. The molecular weights of the product determined by the GPC were lower than were the theoretical values. The result was discussed in light of the chain transfer reaction to the poly(chloromethylstyrene) repeating units. Morphology of the synthesized block copolymers, examined by an atomic force microscopy (AFM), were also compared and discussed.